Effect of Bagasse Compost and Cow Urine Liquid Organic Fertilizer on Growth and Yield of Lettuce Plants (Lactuca sativa L.) - Lubis, Dea Andini; Hafifah, Hafifah; Nazimah, Nazimah; Rafli, Muhammad; Wirda, Zurrahmi (Yayasan Pertanian Tropika Indonesia (YPTI), 2022)
Lettuce (Lactuca sativa L.) is a plant whose leaves are consumed. The consumers of lettuce plants ranged from the lower to the upper-class societies. Fertilization is one of the technologies that need special care to increase the quality and quantity of the plant’s yields. Cow urine is one of the growth regulators that can be used. Not only it is easier to obtain, but also simpler the apply. Bagasse is a waste material that is usually thrown into an open place without further process, which can cause environmental disturbance and bad smell. This research aims to determine the effect of bagasse compost dosage and concentration of cow urine liquid on the growth and yield of lettuce plants. This research used a factorial randomized block design (RCBD) consisting of two factors. First, bassage compost (T) consisting of 0 g/polybag, 100 g/polybag, and 200 g/polybag, and second, cow urine liquid organic fertilizer (C) which also with three levels consisting of 0 ml/liter, 300 ml/liter, and 400 ml/liter of water. The results shows that 100 grams/polybag of bagasse compost and 300 ml/liter of cow urine liquid organic fertilizer each improve lettuce growth. Combined, they significantly enhance plant height, fresh weight, and dry weight.